(untitled) (Revista de Ciências Agroveterinárias, 2019)
Pitaya is a tropical fruit belonging to the Cactaceae family. With high productive, nutritive, economic and social potential for family farming, it is a still little known culture with scarce information on the conditions affecting the germination of its different species. Thus, this study aimed to evaluate the influence of temperature and luminosity on seed germination of three genotypes of pitaya. To evaluate the effect of temperature on the physiological quality of the seeds, the Selenicereus setaceus, Hylocereus undatus (red peel and white pulp) and Hylocereus polyrhizus were used and (pink red peel and red pulp) submitted to seven germination temperatures (15 °C, 20 °C, 25 °C, 30 °C, and 35 °C, and in alternating temperatures: 15-25 ºC and 20-30 ºC, all in a photoperiod of 12 hours). The evaluations were: percentage of germination, germination speed index, and time for occurrence of 50% of germination. For the evaluation of the influence of the luminosity, the seeds were conditioned in bottle wrapped in aluminum foil to protect the seeds from contact with the luminosity and stored in refrigerator at 10 ± 2 °C for 365 days. They were then submitted to the treatment with and without light and kept in BOD for eleven days, when the normal seedling were counted. The temperatures for the maximum physiological performance of the seeds of three species of pitaya were 25 ºC and the alternating 20-30 °C. On the other hand, the unfavorable temperature was 35 °C. The Selenicereus setaceus showed a higher percentage of germination and vigor in all temperatures evaluated. The species evaluated demonstrated to be positive photoblastic.